Double marginalization: an ethnographic-ecological analysis of rural PE teachers’ professional development between urban and underdeveloped areas - Yan, Jihong; Dai, Xinyu (Frontiers in Public Health, 2025)
IntroductionChina’s rapid urbanization has exacerbated challenges in rural education, including resource disparities, shrinking student populations, and teacher shortages. Rural Health and Physical Education (HPE) teachers face acute professional development barriers, directly impacting their well-being and students’ physical health.MethodsThis ethnographic study combines ecological and bioecological lenses to analyze rural HPE teachers’ professional development. Through three-stage sampling, 35 northeastern Chinese HPE teachers participated in semi-structured interviews and fieldwork. Data were thematically analyzed using an ecological-intersectional (E-I) framework across micro (individual), meso (interpersonal), exo (organizational), and macro (sociocultural) levels.ResultsFindings demonstrate ecological interdependencies: Urbanization policies and unequal resource distribution created structural barriers, while school sports culture and support networks mediated outcomes. Teachers’ professional autonomy and rural commitment emerged as key adaptive factors.ConclusionMultilevel interventions are proposed: macro policies (differentiated standards/resource compensation), organizational support (school leadership/home-school collaboration), and individual empowerment (autonomy/innovation training). This study advances the application of intersectional ecological theory in rural education contexts and offers actionable insights for equitable teacher policy development. It advances theoretical understanding of marginalized HPE teachers’ development while offering actionable policy insights with global relevance for underserved educational contexts.